Elektrofotografik dijital baskı sistemlerinde tram çeşitlerinin ve tram sıklığının farklı baskı altı malzemeleri üzerinde basılabilirliğinin incelenmesi - Akbulak, Barış Aydın (My University, 2024)
Bu çalışma, elektrofotografik dijital baskı sistemlerinde kullanılan tram çeşitleri ve tram sıklıklarının farklı baskı altı malzemeleri üzerindeki basılabilirliğini incelemeyi amaçlamaktadır. Dijital baskı teknolojisi, hızla gelişen teknoloji ile baskı endüstrisinde önemli bir yer edinmiş ve kaliteli, tutarlı baskı sonuçları elde etmek için geleneksel yöntemlere kıyasla daha etkili seçenekler sunmaktadır. Araştırma kapsamında, Konica Minolta AccurioPress C12000 modeli kuru tonerli elektrofotografik baskı makinesi kullanılarak iki farklı tipte kağıt üzerinde (Kaplanmış ve Kaplanmış) baskılar gerçekleştirilmiştir. Bu kağıt türleri, baskı kalitesinin farklı baskı altı malzemeleri üzerinde nasıl değiştiğini değerlendirmek amacıyla seçilmiştir. ECI 2002 ISO 12647-2 referans alınarak hazırlanan bir test skalası kullanılarak üç farklı tram çeşidi ve dokuz farklı tram sıklığı ile baskılar yapılmıştır. Tram çeşitleri arasında Dot70, Dot15, Dot190, Dot270, FM1, FM2, FM3, Line150 ve Line200 bulunmaktadır. Tüm baskılar, makinenin temel kalibrasyon ayarlarına sadık kalınarak gerçekleştirilmiş ve sonuçlar Xrite i1 Pro cihazı ile ölçülmüştür. Ölçümler sonucunda gradasyon eğrileri, nokta kazanç eğrileri ve renk evrenleri çıkartılarak PSO Coated v3 standardına göre değerlendirilmiştir. Bulgular, farklı tram çeşitleri ve sıklıklarının baskı kalitesine olan etkilerini ortaya koymuş, Kaplanmış ve Kaplanmış kağıtlar üzerindeki mikroskobik görüntüler, tram noktalarının büyüklüğü ve dağılımının baskı kalitesini nasıl etkilediğini net bir şekilde göstermiştir. Araştırmanın sonuçları, farklı tram çeşitleri ve tram sıklıklarının baskı kalitesine olan etkilerini net bir şekilde ortaya koyarak, baskı kalitesini artırmak ve baskı süreçlerini optimize etmek için önemli bulgular sunmaktadır. Tram sıklığının ve tram çeşidinin, baskı altı malzemesi türüne bağlı olarak baskı kalitesini önemli ölçüde etkilediği görülmüştür. Özellikle, yüksek tram sıklıklarının daha net ve keskin baskılar sağladığı, ancak bazı durumlarda tonlama ve renk doğruluğunda zorluklar yaratabildiği tespit edilmiştir. Bu çalışma, baskı teknolojilerinin geliştirilmesine katkı sağlayacak ve sektörde karşılaşılan teknik problemlerin çözümüne yönelik yeni yaklaşımlar sunacaktır.

This study aims to investigate the printability of different halftone types and frequencies on various substrates in electrophotographic digital printing systems. With rapidly advancing technology, digital printing has become a significant component in the printing industry, offering more effective solutions compared to traditional methods to achieve high-quality and consistent print results. The research involved printing on two different types of paper (matte coated and uncoated) using a Konica Minolta AccurioPress C12000 dry toner electrophotographic printing machine. These paper types were selected to evaluate how print quality varies across different substrates. A test scale prepared with reference to ECI 2002 ISO 12647-2 was used to carry out the prints, employing three different halftone types and nine different halftone frequencies. The halftone types include Dot70, Dot150, Dot190, Dot270, FM1, FM2, FM3, Line150, and Line200. All prints were made adhering to the machine's basic calibration settings, and the results were measured using an Xrite i1 Pro device. Gradation curves, dot gain curves, and color gamuts were derived from the measurements and evaluated according to the PSO Coated v3 standard. The findings highlight the impact of different halftone types and frequencies on print quality, showing how the size and distribution of halftone dots affect print quality on matte coated and uncoated papers. The study's results clearly demonstrate the influence of different halftone types and frequencies on print quality, providing valuable insights for enhancing print quality and optimizing printing processes. It was found that halftone frequency and type significantly affect print quality depending on the substrate type. Specifically, higher halftone frequencies result in sharper and more defined prints but may present challenges in toning and color accuracy in some cases. This research offers significant findings that can contribute to the advancement of printing technologies and propose new approaches to address technical issues faced in the industry. This study contributes valuable knowledge that can help improve print quality and optimize printing processes, addressing various technical challenges within the industry. The findings indicate that halftone frequency and type significantly impact print quality based on the substrate type, with higher frequencies viii providing sharper prints but potentially causing issues with toning and color accuracy. This research is poised to aid in the development of printing technologies and offer new solutions to the industry's technical challenges.
Investigation of the printability of different halftone types and frequencies on various substrates in electrophotographic digital printing systems
Keywords: AM : Amplitude Modulation; Basım makineleri ve gereçleri; Baskı teknikleri; CIE : International Commission on Illumination; CIJ : Continuous Inkjet; CMM : Color Management Module; CMYK : Cyan Magenta Yellow; CMYK : Cyan Magenta Yellow Key; D65 : Daylight 65; DOD : Drop On Demand; DOT : Nokta; DPI : Dots Per Inch; ECI : European Color Initiative; FM : Frequency Modulation; ICC : International Color Consortium; IQ : Intelligent Quality Optimizer; ISO : International Organization for Standardization; KeyD65 : Daylight 65; L*a*b* : Lightness*Red-Green Axis*Yellow-Blue Axis; LINE : Çizgi; LPI : Lines Per Inch; Printing machinery and supplies; Printing techniques; PSO : Process Standard Offset; RGB : Red Green Blue; UV : Ultraviolet; ΔE : İki Renk Arasında ki Farkı İfade Eden Ölçü Birimi; ΔE : İki Renk Arasında ki Farkı İfade Eden Ölçü Birimi AM : Amplitude Modulation